Retracted: Design of LoRa Antenna for Wearable Medical Applications - Amer Alsaraira; Omar A. Saraereh; Ashraf Ali; Samer Alabed (IEEE Access)
The intraoral Tongue Drive System (iTDS) is a wireless assistive technology (AT) that may be operated using a variety of user-defined voluntary tongue motions. In this study, we introduce a novel arch-shaped iTDS that takes up the buccal shelf space in the mouth without constricting tongue motions. Damage to the central nervous system that causes upper limb paralysis. For instance, severe spinal cord injuries, certain strokes or multiple amputations of the upper limbs can make it very difficult for a lot of individuals to go about their everyday lives since they cause them to lose function, control, and independence. Because its muscles are strong and dexterous and do not quickly tire when not necessary to exert power, the tongue is an excellent choice for controlling an AT. Additionally, through cranial nerves, which are unaffected by a spinal cord damage, the tongue is directly attached to the brain. Furthermore, since the tongue movements may be totally hidden from view, TDS-based AT safeguard users’ privacy. In order to provide an effective solution, this paper proposed a novel antenna design with dual-band and implantability. The antenna is modelled in single-layer human muscle considering the feasibility and computational time. Then, the performance is evaluated through multi-layered human oral cavity model. A protective layer is established to prevent direct contact between the antenna and human body. Simulation results show that the proposed antenna has better reflection coefficient, impedance, and radiation pattern as compared with existing antennas.